Biomass-based adsorbents for post-combustion CO2 capture: Preparation, performances, modeling, and assessment. (15th February 2023) - Zhu, Shaoliang; Zhao, Bingtao; Zhang, Haonan; Su, Yaxin
Abstract: The adsorbents are critical carriers in the process of adsorption-based post-combustion CO2 capture. Biomass-based adsorbents (BAs) are considered to have great potential because of their high efficiency, low cost, and good sustainability. To understand the methods, theories, and technologies of BAs-based CO2 capture, this work analyzes their preparation and activation/modification, influencing factors, mechanisms, thermodynamics/kinetics, regeneration and cycle performances, and the pathway to application. It is found that BAs prepared by pyrolysis, chemical activation, and modification with dual heteroatoms are more conducive to improving adsorption sites. CO2 adsorption capacity positively correlates with elemental C and fixed carbon of feedstocks, but negatively with moisture. The BAs prepared at 550–600 °C have high performance. The specific surface area (SSA) increases as the preparation time increases by 9.4%–93.4%. The adsorption capacity is positively correlated to the SSA (R = 0.880) and microporous volume (R = 0.773). Moreover, it decreases linearly with increasing operating temperature with the slope of −0.6 mmol/(g·°C) but increases exponentially with increasing operating pressure and CO2 concentration with the power of 0.824. The adsorption process includes physical and/or physicochemical adsorption. Freundlich isotherm equation and pseudo-second-order model characterize the adsorption thermodynamics and kinetics more effectively with R 2  = 0.985–1.000 and R 2  = 0.894–1.000. The quantum chemistry indicates that most BAs modified with non-metallic belong to physisorption. The regeneration of BAs has low energy consumption (<3.44 MJ/kg CO2 ) and loss rate (<8%). Furthermore, the technical pathway is proposed for application. Finally, the challenges are also presented to facilitate the development of BAs–CO2 capture. Graphical abstract: Image 1 Highlights: Current status and challenges in biomass-based adsorbents for CO2 capture. Optimal preparation methods and effects of operating parameters are addressed. Thermodynamics, kinetics, and microscopic mechanisms are explored. Techno-economic performances and applications are assessed and developed.